2021
DOI: 10.1021/acs.jpca.1c06537
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction N(2D) + CH3CCH (Methylacetylene): A Combined Crossed Molecular Beams and Theoretical Investigation and Implications for the Atmosphere of Titan

Abstract: The reaction of excited nitrogen atoms N( 2 D) with CH 3 CCH (methylacetylene) was investigated under single-collision conditions by the crossed molecular beams (CMB) scattering method with mass spectrometric detection and time-of-flight analysis at the collision energy ( E c ) of 31.0 kJ/mol. Synergistic electronic structure calculations of the doublet potential energy surface (PES) were performed to assist the interpretation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…The resulting beam velocity and speed ratio were 2283 m/s and 5.4, respectively. In our previous experiments on the reactions of N atoms with saturated and unsaturared hydrocarbons, we verified that the presence of N­( 4 S) and N­( 2 P) in the nitrogen beam did not affect the experimental outcomes, because the rate coefficients of the N­( 4 S) and N­( 2 P) reactions with saturated and unsaturated hydrocarbons are much smaller than those of N­( 2 D). ,, In addition, the extra energy carried by the 2 P state was never necessary to fit the experimental data. Analogous to the case of N­( 2 D) + C 2 H 4 , we expect that the reactions involving N­( 4 S) and N­( 2 P) + vinyl cyanide do not contribute to the reactive signal.…”
Section: Experimental and Theoretical Methodssupporting
confidence: 55%
See 3 more Smart Citations
“…The resulting beam velocity and speed ratio were 2283 m/s and 5.4, respectively. In our previous experiments on the reactions of N atoms with saturated and unsaturared hydrocarbons, we verified that the presence of N­( 4 S) and N­( 2 P) in the nitrogen beam did not affect the experimental outcomes, because the rate coefficients of the N­( 4 S) and N­( 2 P) reactions with saturated and unsaturated hydrocarbons are much smaller than those of N­( 2 D). ,, In addition, the extra energy carried by the 2 P state was never necessary to fit the experimental data. Analogous to the case of N­( 2 D) + C 2 H 4 , we expect that the reactions involving N­( 4 S) and N­( 2 P) + vinyl cyanide do not contribute to the reactive signal.…”
Section: Experimental and Theoretical Methodssupporting
confidence: 55%
“…RRKM calculations for the N­( 2 D) + CH 2 CHCN reaction were performed using a code implemented in our group for this purpose. ,, The microcanonical rate constant k ( E ) for a specific reaction at a specific total energy is given by the expression where N ( E ) represents the sum of states at the transition state at energy E , ρ­( E ) is the density of states of the reactant, and h is Planck’s constant. N ( E ) is obtained by integrating the relevant density of states up to energy E , and the rigid rotor/harmonic oscillator model is assumed.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 20 When reacting with hydrocarbons, molecular products possessing a novel C–N bond are formed. 9 14 , 18 − 20 Recent kinetic experiments performed with the CRESU technique at the relevant temperature for the conditions of the upper atmosphere of Titan have revealed that the rate constants for several important N( 2 D) reactions are considerably larger 21 , 22 or smaller 23 than those determined by previous experiments above 200 K. 24 − 26 The inclusion of these data in updated versions of a photochemical model of the atmosphere of Titan have demonstrated the importance of this approach in making the model more accurate. 21 − 23…”
Section: Introductionmentioning
confidence: 99%